Performance verb derivation of dynamic spatial lokalizovanosti prefixed with you-, in the Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article is devoted to the analysis of word-formative ability of the verbs of dynamic dimensional locality withe the prefix ви-. The structure of the typical word-formative paradigm of the analized formatives is established, as well as the quantitative fullness of enery structural block and word-formative meaning is determined.
Keywords: prefixal verb; typical word-formative paradigm; word-formative meaning; derivative potential; derivative